Coupled Thermo-Hydro-Mechanical Simulation of Geological Porous Media - Byström, Fanny (My University, 2017)
Countries around the globe have battled with the issue of nuclear waste for decades and the solution appears to be underground repositories. To assure its safety, both experimental and numerical testing is essential. In this master’s thesis, a numerical model has been developed in the software STAR-CCM+ with the intention of capturing the difficult thermo-hydro-mechanical (THM) coupling that occurs in porous rocks as a result of thermal loads. Results show that the respective mechanisms have been captured differently well. The thermal field is highly similar to that in the reference experiment while the pressure and displacement deviate to a higher extent. It was experienced difficult to identify "the villain of the piece", but the problems could possibly have originated from the numerical set-up not being ideal (highly sensitive simulation), assumptions and simplifications or weaknesses in the software that has a relatively newly introduced stress model. Furthermore, it is worth mentioning that, though the pressure and displacement are higher than expected, they still follow the correct behaviour throughout the simulation. Additionally, a sensitivity study was made that revealed the case’s strong dependence on the heat source and permeability of the rock. Concluding remarks include that THM coupling is highly complex and numerically sensitive. While a model was achieved and deemed relatively satisfactory, it is not yet completely reliable and accurate. To possibly accomplish this, further work is required in the form of general troubleshooting and a reduction of simplifications including for example the use of isotropy and constant values for parameters such as porosity and permeability. It is also advised to consider validating/trouble-shooting the model by using a different software, especially for the stress model.
Keywords: Energi; Hållbar utveckling; Strömningsmekanik; Energy; Sustainable Development; Fluid mechanics